(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objectives: To identify the guidelines provided to patients with venous ulcers submitted to telenursing and describe the outcome that occurred with patients with venous ulcers monitored remotely. Method: Cross-sectional and documentary study, carried out with 159 medical records of patients with venous ulcers submitted to telenursing at an enterostomal therapy clinic in Rio de Janeiro, Brazil. The inclusion criteria were patients with a diagnosis of venous ulcer submitted to Telenursing, from April 2018 to February 2020. Data analysis was performed using descriptive statistics (absolute and relative frequency for categorical variables), aided by the application spreadsheet Microsoft Excel. Results: A balance was identified between the participants in relation to gender; had a mean age (standard deviation) of 68.07 (5.28); completed elementary school or incomplete high school; retirees or pensioners. It was found that 40.88% of the patients had at least one underlying disease,predominantly systemic arterial hypertension and diabetes mellitus. The most prevalent guidelines were: resting with the lower limbs elevated, using compressive therapy with elastic stockings or elastic bandage, and changing the secondary dressing at home. Conclusion: The findings show the need to expand the nursing actions developed at the clinic, seeking to provide comprehensive health to patients.